2023
DOI: 10.1190/geo2022-0628.1
|View full text |Cite
|
Sign up to set email alerts
|

An improved elastic wavefield separation method based on the Helmholtz decomposition

Abstract: Elastic wave-mode separation plays an important role in elastic reverse-time migration (RTM) and elastic full-waveform inversion. It helps to remove crosstalk artifacts and improve imaging quality. A class of efficient methods for elastic wave-mode separation in isotropic elastic media is the Helmholtz decomposition technique. Although this kind of approach produces pure-mode vector wavefields with correct amplitudes, phases, and physical units, their computational costs are still high especially for 3D large-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…(2018), in recent years, reverse‐time migration (RTM) (Baysal et al., 1983;McMechan, 1983; Whitemore, 1983) has become a powerful practical tool for prestack imaging in the exploration and production of oil and gas reservoirs. Currently, the wavefield decoupling techniques in isotropic media (Ma & Zhu, 2003; Li et al., 2007; Zhang et al., 2007; Xiao & Leaney, 2010; Wang & McMechan, 2015; Zheng & Yao, 2023; Zhu, 2017) have become relatively mature and are widely used in elastic RTM (ERTM) (Du et al., 2017, 2020; Zhang & Lu., 2022; Zhou et al., 2019; Zhu, 2017) and full waveform inversion (Qu et al., 2018; Ren & Liu, 2016; Sears et al., 2008; Wang & Cheng, 2017). However, due to the fact that the polarization direction of waves in anisotropic media is neither parallel nor perpendicular to the direction of wave propagation, there are coupling or interference phenomena between the separated P‐ and S‐wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018), in recent years, reverse‐time migration (RTM) (Baysal et al., 1983;McMechan, 1983; Whitemore, 1983) has become a powerful practical tool for prestack imaging in the exploration and production of oil and gas reservoirs. Currently, the wavefield decoupling techniques in isotropic media (Ma & Zhu, 2003; Li et al., 2007; Zhang et al., 2007; Xiao & Leaney, 2010; Wang & McMechan, 2015; Zheng & Yao, 2023; Zhu, 2017) have become relatively mature and are widely used in elastic RTM (ERTM) (Du et al., 2017, 2020; Zhang & Lu., 2022; Zhou et al., 2019; Zhu, 2017) and full waveform inversion (Qu et al., 2018; Ren & Liu, 2016; Sears et al., 2008; Wang & Cheng, 2017). However, due to the fact that the polarization direction of waves in anisotropic media is neither parallel nor perpendicular to the direction of wave propagation, there are coupling or interference phenomena between the separated P‐ and S‐wave.…”
Section: Introductionmentioning
confidence: 99%
“…In order to tackle this issue, a new pseudo‐Helmholtz operator based on the wavefront phase direction was proposed, and the generalized minimum residual algorithm was utilized to iteratively solve the Poisson equation for the acquisition of separated vector P‐ and S‐wavefields. Zheng and Yao (2023) introduced a scalar Poisson equation and developed a fast solver for it, enabling wavefield separation in isotropic media. They suggested that this method can be extended to anisotropic media.…”
Section: Introductionmentioning
confidence: 99%